Mapping Region in Early American Writing - Watts, Edward, 1964-; Holt, Keri; Funchion, John (Book collections on Project MUSE., 2015)
"The essays collected in Mapping Regions in Early American Writing study how American writers thought about the spaces around them. The contributors reconsider the various roles regions--imagined politically, economically, racially, and figuratively--played in the formation of American communities, both real and imagined. The texts they study--some canonical, others archival, some literary, others scientific, polemical, or documentary--create and reveal important mental mappings and cartographies that reveal how a diversity of populations imagined themselves, their communities, and their nation as occupying various places in the American landscape"--Provided by publisher.